SHAPED OBJECTS BASED ON MODIFIED BIOCHAR AND A POLYMER AND METHODS FOR PRODUCING THEM - GOULD, Oliver Edward Christopher; SCHWAAG, Daniel; LONGÁN RODRÍGUEZ, Victoria (2024)
Subject of the invention is a method for producing a shaped object for construction applications, comprising the steps (a) providing a biochar in particulate form, which has been subjected to an oxidation reaction, (b) subjecting the biochar to a coupling reaction with a silane coupling agent, (c) mixing the biochar with a polymer, and (d) moulding the mixture. The invention also relates to shaped objects and construction materials which are obtainable by the method, and to a biochar material. L'invention concerne un procédé de production d'un objet façonné pour des applications de construction, comprenant les étapes consistant à (a) fournir un charbon de biomasse sous forme particulaire, qui a été soumis à une réaction d'oxydation, (b) soumettre le charbon de biomasse à une réaction de couplage avec un agent de couplage au silane, (c) mélanger le charbon de biomasse avec un polymère, et (d) mouler le mélange. L'invention concerne également des objets façonnés et des matériaux de construction qui peuvent être obtenus par le procédé, et un matériau de charbon de biomasse.